功率分流式行星锥无级变速器的设计研究 - 张明成 (Jixie chuandong)
The Power-dividing planet-cone continuously variable transmission is the combined CVT which the plane-cone CVT acts as its enclosed mechanism, and 2KH acts as fundamental mechanism. The combination principal of the combined CVT is analyzed and its formula of the transmission ratio is obtained. The transmitting condition of non-circulation power circuit is analyzed. In order to reveal wether the transmission is feasible, the transmitting conditions are elucidated. The gear ratio of two central gears of the fundamental mechanism （differential gear train） is analyzed on how to affect the circulation around circuit. The maximal transmitting power of the planetary mechanism （planet-cone CVT） is analyzed. And the formula of the input power and mechanism dimensions which may become the designing criteria are given.